Academic libraries in Leyte a survey with implications for library cooperation - Yap, Lilybelle D. (Institute of Library Science, University of the Philippines Diliman, 1990)
This descriptive research is a survey of the resources and facilities of the academic libraries in Leyte for the possibility of establishing library cooperation among them. Specifically, the study aims to 1) describe existing resources and facilities of academic libraries in Leyte; 2) determine the extent of library cooperation among academic institutions in Leyte; 3) find out the attitudes of the librarians in this area regarding library cooperation and resource sharing; 4) recommend possible areas where library cooperation and resource sharing can be undertaken among libraries in Leyte.